2020
DOI: 10.3197/np.2020.240102
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Multiple Drivers of Pastoral Fulani Migration to Ghana

Abstract: The relationship between environmental change and migration has generated considerable scholarly debate. In part the literature suggests that climate change in the Sahel is 'forcing' pastoralist groups (mainly Fulani) to migrate to semi-arid West African countries, including Ghana, due to resource scarcity and climatic conditions. Using interviews, focus-group discussions and observations, this article argues that beyond theoretical postulations on resource scarcity and environmentally induced migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…I come back when the soldiers are not shooting (Herder, Koworeso, 2019).This showed that the herdsmen feared encounters with security agents more than encounters with farmers. This narration by the herder resonates with findings of Bukari et al (2020) who found similarly that herders in Agogo and Gushiegu use migration to other places within and outside as a way to escape violent conflicts. Similarly, Turner (2004) notes that migration to far places is often the main strategy used by pastoralists to escape conflicts with farmers and other pastoralists over water and pastureland.…”
Section: Nonforced Migration As a Cognitive Strategysupporting
confidence: 78%
“…I come back when the soldiers are not shooting (Herder, Koworeso, 2019).This showed that the herdsmen feared encounters with security agents more than encounters with farmers. This narration by the herder resonates with findings of Bukari et al (2020) who found similarly that herders in Agogo and Gushiegu use migration to other places within and outside as a way to escape violent conflicts. Similarly, Turner (2004) notes that migration to far places is often the main strategy used by pastoralists to escape conflicts with farmers and other pastoralists over water and pastureland.…”
Section: Nonforced Migration As a Cognitive Strategysupporting
confidence: 78%
“…This criticism has also been levelled at some of the models used to project future scenarios for environmentally induced migration (Bukari et al 2020). Moreover, populations' perceptions of environmental change, upon which they base their migration decisions, do not necessarily align with externally observed climate data (De Longueville et al 2020).…”
Section: Three Phenomena: Migration Displacement and Immobilitymentioning
confidence: 99%
“…Shifts in land-use and land tenure have affected livestock mobility, rangeland status, livestock productivity, and herd sizes, and, ultimately, food production, food security, and pastoralists' welfare. Reviews by Galvin (2009), Reid et al (2014), andCoppock et al (2017) highlighted the roles of land privatization, pastoralist sedentarization, cropland expansion, farmer-herder conflict, protected area delimitation, and large-scale land grabbing and acquisition, in fragmenting rangelands and constraining animal mobility (see also Bukari et al, 2020;Turner et al, 2014Turner et al, , 2016. The lack of legislation and policies supporting local and regional livestock movements, as in some countries of the Sahel, is another factor promoting more sedentary and less productive livestock husbandry (Gonin and Gautier, 2015).…”
Section: Land-use and Management Practicesmentioning
confidence: 99%
“…Finally, at the global scale, food and energy security concerns of actors located outside of drylands are emerging threats to the food security of dryland dwellers. Large-scale land acquisitions (LSLAs) for commercial agriculture by foreign governments and corporations are driving direct and indirect land-use change, cropland and pasture alienation, and displacement of local communities (Bukari et al, 2020;Galaty, 2013;Koizumi, 2015;Schlee, 2013), thus adversely affecting their food availability and access. Pastoral rangelands' common property regimes make them particularly vulnerable to such land grabs (Dell'Angelo et al, 2017).…”
Section: Land-use and Management Practicesmentioning
confidence: 99%